2008
DOI: 10.1007/s00423-007-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged high mortality rates from acute occlusive intestinal ischemia: six year review

Abstract: AII remains a highly lethal condition. Mortality rates remain as high as they did decades ago due in part to advanced presentation and advanced age with multiple associated conditions and risk factors, all of which are independent predictors of adverse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
147
5
21

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(179 citation statements)
references
References 30 publications
6
147
5
21
Order By: Relevance
“…1,11 Kassahun et al reported survival rate of 50% in patients diagnosed within first 24 hours and less than 30% in those presenting after 24 hours of symptoms. 12 Majority of the times the delay in presentation to our tertiary referral centre was due to delayed referral from other hospitals due to diagnostic dilemma. Thus early admission and early diagnosis4 and treatment before gangrene sets in or progresses is vital for favourable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 Kassahun et al reported survival rate of 50% in patients diagnosed within first 24 hours and less than 30% in those presenting after 24 hours of symptoms. 12 Majority of the times the delay in presentation to our tertiary referral centre was due to delayed referral from other hospitals due to diagnostic dilemma. Thus early admission and early diagnosis4 and treatment before gangrene sets in or progresses is vital for favourable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the considerable advances in the diagnosis and treatment of such patients and a better understanding of the pathophysiology of the disease, the mortality and morbidity still remain high [8]. The reasons for this are manifold.…”
Section: Discussionmentioning
confidence: 99%
“…Yaşlı hastalarda bazı kriterler (>84 yaş, bandemi, batında serbest hava) yüksek mortalite, bazı kriterler ise (hipotansiyon, anormal barsak sesleri, masif dilate barsak ansları ve aşırı lökositoz) ise cerrahi müdahale gereksinimi ile ilişkilendirelebilirler, ancak bu kriterlerin yokluğu ciddi bir sorun olmadığı anlamına gelmemektedir. Viral gastroenteritlerin yaşlıda seyrek olduğunu, fakat ortaya çıkan ishallerin %31-40'ında altta yatan mezenter iskemi olduğununda unutulmaması önemlidir (24)(25)(26). Akut karın ağrısı ile acil servise başvuran geriatrik yaş grubunun incelendiği bir çalışmada ise; hastaların %60'nın yatarak izlendiği, %20'sinde invaziv bir girişim yapıldığı, taburcu edilen hastaların %10'unun yeniden acil servise başvurduğu ve daha da dramatik olarak % 5'inin iki haftalık takip süresi içinde hayatını kaybettiği saptanmıştır (9).…”
Section: Tanı Koymada Güçlüklerunclassified